Dynamic Volatility Modeling of Indonesian Insurance Company Stocks - Budiandru Budiandru (Jurnal Ekonomi dan Studi Pembangunan, 2022)
The Indonesian capital market is one of the investment destination countries for investors in developed countries. The development of economic conditions in Indonesia itself is considered suitable for investors to invest. Insurance sector stocks are one of the sectors that are the target of investors. This study predicts the share price of insurance companies. Data in daily form from 2010 to 2020 uses the Autoregressive Conditional Heteroskedasticity - Generalized Autoregressive Conditional Heteroscedasticity (ARCH - GARCH) method. The results showed that forecasting that was carried out until 2025 all the insurance companies studied experienced an upward trend in stock prices. Investors can manage their funds by increasing or decreasing the insurance stock portfolio and adjusting the asset allocation with the investment strategy.